2015
DOI: 10.1111/ppa.12389
|View full text |Cite
|
Sign up to set email alerts
|

Dothistroma needle blight: an emerging epidemic caused by Dothistroma septosporum in Colombia

Abstract: Plantation forestry in Colombia is based mainly on non-native species of Pinus and Eucalyptus. Since 2008, a disease with symptoms similar to those of dothistroma needle blight (DNB) has been found affecting large areas planted to Pinus spp. The aim of this study was to identify the causal pathogen as well as to document the levels of disease incidence and severity. Isolates from each of three forestry zones, collected from different host species, were compared based on rDNA sequence of the ITS regions. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Field‐based evidence of the rapid expansion that DNB is capable of under such optimal conditions has recently been observed in Colombia (Rodas et al. ).…”
Section: The Influence Of Weather On Dothistroma Needle Blightmentioning
confidence: 99%
“…Field‐based evidence of the rapid expansion that DNB is capable of under such optimal conditions has recently been observed in Colombia (Rodas et al. ).…”
Section: The Influence Of Weather On Dothistroma Needle Blightmentioning
confidence: 99%
“…In New Zealand, Gilmour (1981) showed that peaks in disease severity coincided with periods of rainfall, with little or no infection during dry periods. Other studies in Britain, Bulgaria, Hungary, Canada, USA, Chile, Colombia and Kenya also noted a clear link between high summer rainfall and high disease severity (Archibald & Brown, 2007;Dubin, 1967;Fraser, Mullett, Woodward, & Brown, 2016;Gibson et al, 1964;Koltay, 2015;Murray & Batko, 1962;Rodas et al, 2016;Rogerson, 1953;Woods et al, 2005;Zlatanov, 1977).…”
Section: Factors Contributing To Disease Developmentmentioning
confidence: 91%
“…In New Zealand, Gilmour (1981) showed that peaks in disease severity coincided with periods of rainfall, with little or no infection during dry periods. Other studies in England, Bulgaria, Hungary, Canada, USA, Chile, Colombia and Kenya also noted a clear link between high summer rainfall and high disease severity (Rogerson 1954;Murray and Batko 1962;Gibson et al 1964;Dubin 1967;Zlatanov 1977;Woods et al 2005;Archibald and Brown 2007;Fraser et al 2016b;Koltay 2015;Rodas et al 2015).…”
Section: Factors Contributing To Disease Developmentmentioning
confidence: 93%
“…; Rodas et al. ). The disease is characterized by red bands or spots surrounding black fruiting structures on infected pine needles (Peterson and Walla ).…”
Section: Introductionmentioning
confidence: 97%